Ozone depletion due to dust release of iodine in the free troposphere - Koenig, Theodore K. (2021)
Iodine is an atmospheric trace element emitted from oceans that efficiently destroys ozone (O3). Low O3 in airborne dust layers is frequently observed but poorly understood. We show that dust is a source of gas-phase iodine, indicated by aircraft observations of iodine monoxide (IO) radicals inside lofted dust layers from the Atacama and Sechura Deserts that are up to a factor of 10 enhanced over background. Gas-phase iodine photochemistry, commensurate with observed IO, is needed to explain the low O3 inside these dust layers (below 15 ppbv; up to 75% depleted). The added dust iodine can explain decreases in O3 of 8% regionally and affects surface air quality. Our data suggest that iodate reduction to form volatile iodine species is a missing process in the geochemical iodine cycle and presents an unrecognized aeolian source of iodine. Atmospheric iodine has tripled since 1950 and affects ozone layer recovery and particle formation.